Proceedings 2000 Australian Software Engineering Conference
DOI: 10.1109/aswec.2000.844576
|View full text |Cite
|
Sign up to set email alerts
|

A survey of software development practices in the New Zealand software industry

Abstract: We report on the software development techniques used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 4 publications
1
42
1
Order By: Relevance
“…Groves et al [5] reported on the software development techniques used in the New Zealand software industry, paying particular attention to requirements gathering. They surveyed a selection of software companies with a general questionnaire and then conducted in-depth interviews with four companies.…”
Section: Related Workmentioning
confidence: 99%
“…Groves et al [5] reported on the software development techniques used in the New Zealand software industry, paying particular attention to requirements gathering. They surveyed a selection of software companies with a general questionnaire and then conducted in-depth interviews with four companies.…”
Section: Related Workmentioning
confidence: 99%
“…In these studies there was a use of questionnaires and telephone interviews, it was sent to 65 companies and interview was also conducted with senior members of each company [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…The applications in Organisations B, and D would be classified in the Pressman typology as new developments, responding to customer requests, that in Organisation C a re-engineering project and in Organisation E an application enhancement. There was also an element of concept development in the project undertaken by Organisation E. The kinds of product development undertaken were one-off contracts (Organisations A and C), in house development (Organisations B and D) and mass production in Organisation E. The size of a project can be categorised, in a New Zealand context, according to the number of people involved with the development process where less than three is small, from three to nine medium, and greater than ten is large (Groves et al, 2000). Given this classification scheme, the only large project was undertaken by Organisation C with all the others medium in size.…”
Section: Developermentioning
confidence: 99%
“…meeting customer requests), application enhancements (corrections or upgrades), application maintenance or re-engineering legacy systems (Pressman, 2001). Another way of looking at a project is to determine what Groves et al (2000) call the kind of development undertaken by a company. They distinguish between specific products for customers (one-off contracts or mass production), in house software to support the running of the organisation and product support where software is included in goods sold by the company.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation